Cell Surface-Associated Elongation Factor Tu Mediates the Attachment of Lactobacillus johnsonii NCC533 (La1) to Human Intestinal Cells and Mucins - Granato, Dominique (American Society for Microbiology, 2004)
The aim of this work was to identify Lactobacillus johnsonii NCC533 (La1) surface molecules mediating attachment to intestinal epithelial cells and mucins. Incubation of Caco-2 intestinal epithelial cells with an L. johnsonii La1 cell wall extract led to the recognition of elongation factor Tu (EF-Tu) as a novel La1 adhesin-like factor. The presence of EF-Tu at the surface of La1 was confirmed by analysis of purified outer surface protein extract by immunoblotting experiments, by electron microscopy, and by enzyme-linked immunosorbent assays of live bacteria. Furthermore, tandem mass spectrometry analysis proved that EF-TU was expressed at the La1 surface as an intact molecule. Using recombinant La1 EF-Tu protein, we were able to determine that its binding to intestinal cells and to mucins is pH dependent. Competition experiments suggested that EF-Tu has an important role in La1 mucin binding capacity. In addition, immunomodulation studies performed on HT29 cells showed that EF-Tu recombinant protein can induce a proinflammatory response in the presence of soluble CD14. Our in vitro results indicate that EF-Tu, through its binding to the intestinal mucosa, might participate in gut homeostasis.